If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 84 = u + 6 Reorder the terms: 84 = 6 + u Solving 84 = 6 + u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. 84 + -1u = 6 + u + -1u Combine like terms: u + -1u = 0 84 + -1u = 6 + 0 84 + -1u = 6 Add '-84' to each side of the equation. 84 + -84 + -1u = 6 + -84 Combine like terms: 84 + -84 = 0 0 + -1u = 6 + -84 -1u = 6 + -84 Combine like terms: 6 + -84 = -78 -1u = -78 Divide each side by '-1'. u = 78 Simplifying u = 78
| (21-2x)*(29.7-2x)*x-1000=0 | | [n-3]*4=28 | | 4x-2(x+5)=-8+4x+12 | | -x^2+10x+24=0 | | 7(x+6)=-28 | | -5+300=75 | | 6(2x-7)=-5(3x-15) | | 539=5x^2+13x | | 2x+3y=396 | | 3x+3=5x-2 | | x^2-25=0equation | | x+2(-13+8x)=6 | | (X-4)10=7x+11 | | n^2+18n+96=0 | | n^2+18+96=0 | | 8-M=3M+16 | | 3x+51/4=3 | | 3xy+4xy+5x(5x)y+6xy(2)= | | 4(x-2)=8x-(8+4x) | | Y=20x+100 | | 6x/9=18 | | 4x^2+15x-10=0 | | 4a+4=a | | 3x+48/8=3 | | 7=w+3 | | -4v-10=-v+2 | | .15x^2-3x+30=0 | | -15y+-10y= | | (x(a-1)+a)(x(b-1)+b)=-2x+bx+ax+a+b | | 10-(2x+4)=7-3x | | -12u-18=-12u-18 | | 1-4x^2=-8 |